Autotransporters and Their Role in the Virulence of Burkholderia pseudomallei and Burkholderia mallei - Lazar Adler, Natalie; Stevens, Joanne; Stevens, Mark; Galyov, Edouard (Frontiers in Microbiology, 2011)
Burkholderia pseudomallei and Burkholderia mallei are closely related Gram-negative bacteria responsible for the infectious diseases melioidosis and glanders, respectively. Autotransporters (ATs) comprise a large and diverse family of secreted and outer membrane proteins that includes virulence-associated invasins, adhesins, proteases and actin-nucleating factors. The B. pseudomallei K96243 genome contains eleven predicted ATs, eight of which share homologues in the B. mallei ATCC 23344 genome. This review distils key findings from in silico, in vitro and in vivo studies on the ATs of B. pseudomallei and B. mallei. To date, the best characterized of the predicted ATs of B. pseudomallei and B. mallei is BimA, a predicted trimeric AT mediating actin-based motility which varies in sequence and mode of action between Burkholderia species. Of the remaining eight predicted B. pseudomallei trimeric autotransporters, five of which are also present in B. mallei, two (BoaA and BoaB), have been implicated in bacterial adhesion to epithelial cells. Several predicted Burkholderia ATs are recognized by human humoral and cell-mediated immunity, indicating that they are expressed during infection and may be useful for diagnosis and vaccine-mediated protection. Further studies on the mode of secretion and functions of Burkholderia ATs will facilitate the rational design of control strategies.